1992
DOI: 10.1093/ajcn/55.5.1012
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and platelet aggregation: the Caerphilly Prospective Heart Disease Study

Abstract: Intakes of alcohol and saturated fatty acids were determined through a dietary questionnaire from 1600 men (aged 49-66 y) in the Caerphilly Prospective Heart Disease Study. Platelet aggregation induced by thrombin adenosine disphosphate (ADP), and collagen was studied in subjects who had fasted and had not recently taken drugs affecting platelets. In subjects who drank alcohol, the odds ratio of a high response to aggregation was significantly reduced (primary ADP, P less than 0.05; secondary ADP, P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(102 citation statements)
references
References 29 publications
0
98
0
4
Order By: Relevance
“…22a Several plausible biological mechanisms have been proposed to explain the inverse association between alcohol and CHD among general populations. In addition to increasing the levels of HDL cholesterol and its subfractions, 10,23 alcohol has also been shown to decrease platelet aggregation 24,25 and increase fibrinolytic activity. 26 These hypothesized mechanisms could be even more important in a diabetic population, in which dyslipidemia and coagulation disorders are more prevalent than they are in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…22a Several plausible biological mechanisms have been proposed to explain the inverse association between alcohol and CHD among general populations. In addition to increasing the levels of HDL cholesterol and its subfractions, 10,23 alcohol has also been shown to decrease platelet aggregation 24,25 and increase fibrinolytic activity. 26 These hypothesized mechanisms could be even more important in a diabetic population, in which dyslipidemia and coagulation disorders are more prevalent than they are in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…In the Caerphilly Prospective Heart Disease Study (23) it appears that the intake of alcohol was inversely associated with the response of platelets to aggregation induced by collagen and ADP. Since, it has been demonstrated that, like aspirin (24), alcohol inhibits the secondary aggregation; it can be postulated that alcohol inhibits the release of TXA2 induced by different agonists (25,26).…”
Section: Aggregationmentioning
confidence: 99%
“…A protective vascular effect of moderate alcohol consumption may be mediated by increased high density lipoprotein cholesterol levels (17,18), decreased platelet adhesiveness (19), inhibition of coagulation (20), or enhanced fibrinolysis (21). In a population-based autopsy study, hyalinization of renal arterioles was inversely correlated with alcohol consumption (22).…”
Section: A Protective Effect Of Moderate Alcohol Consumption?mentioning
confidence: 99%